The squire's tale - Morris, Gerald, 1963- (Houghton Mifflin, 1998)
In medieval England, fourteen-year-old Terence finds his tranquil existence suddenly changed when he becomes the squire of the young Gawain of Orkney and accompanies him on a long quest, proving Gawain's worth as a knight and revealing an important secret about his own true identity.